2012
DOI: 10.1063/1.3676049
|View full text |Cite
|
Sign up to set email alerts
|

Permanent magnet online magnetization performance analysis of a flux mnemonic double salient motor using an improved hysteresis model

Abstract: The concept of the memory motor is based on the fact that the magnetization level of the AlNiCo permanent magnet in the motor can be regulated by a temporary current pulse and memorized automatically. In this paper, a new type of memory motor is proposed, namely a flux mnemonic double salient motor drive, which is particularly attractive for electric vehicles. To accurately analyze the motor, an improved hysteresis model is employed in the time-stepping finite element method. Both simulation and experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…2(a), each stator pole consists of two iron teeth and a rectangular PM sandwiched between them and is embraced by a concentrated armature coil, while the inner and outer rotor is simply formed with an iron tooth [16][17][18][19]. Due to both the PMs and armature windings are contained in the middle stator, and a robust piece rotor is similar to the switched reluctance machine [22][23][24][25][26][27][28][29], the BLDR-FSPM motor is well suited to high-speed applications and efficient power generation [30][31][32]. The stator also equips with connecting bridge, magnetic bridge and nonmagnetic material pieces in middle position of iron core.…”
Section: Stator Topologiesmentioning
confidence: 99%
“…2(a), each stator pole consists of two iron teeth and a rectangular PM sandwiched between them and is embraced by a concentrated armature coil, while the inner and outer rotor is simply formed with an iron tooth [16][17][18][19]. Due to both the PMs and armature windings are contained in the middle stator, and a robust piece rotor is similar to the switched reluctance machine [22][23][24][25][26][27][28][29], the BLDR-FSPM motor is well suited to high-speed applications and efficient power generation [30][31][32]. The stator also equips with connecting bridge, magnetic bridge and nonmagnetic material pieces in middle position of iron core.…”
Section: Stator Topologiesmentioning
confidence: 99%
“…Comparing Equations (14) and (19), it is found that cogging torque and back EMF will be reduced at the same time if t equals one. Figure 11 shows the relationship among the step number N, SkewVν,N and t. It can be seen that big value of t is corresponding to big SkewVν,N for the different step number.…”
Section: Analysis Of Rotor Step Skewingmentioning
confidence: 99%
“…Therefore, this kind of AL-PMSM cannot make full use of the PMs and increases the PMs cost. In recent years, flux reverse permanent-magnet machine (FRPM), double salient permanent-magnet machine (DSPM) and flux-switching permanent-magnet machine (FSPM) have been widely investigated due to the advantages of simple and robust rotor structure that is composed of cheap iron core with salient tooth [11][12][13][14][15]. Since the armature windings and the permanent magnets are both installed in the stator of these structures, they can protect the PMs from sliding off caused by centrifugal force and from demagnetizing caused by the heat dissipation difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of EVs, the machine should meet the requirements of high power density and high efficiency in a limited space [1]- [2].It's well known that flux-switching permanent machine(FSPM) [3]- [6] and permanent magnet synchronous machines (PMSM) [7]- [8] have been widely applied to EVs due to their advantages of structural compactness. The concept of double-stator machine is a motor which consist of an inner machine and an outer machine, aiming to improve the torque density and efficiency of machine.…”
Section: Introductionmentioning
confidence: 99%